Bronchoalveolar lavage fluid IMMY Sona Aspergillus lateral-flow assay for the diagnosis of invasive pulmonary aspergillosis: a prospective, real life evaluation. (21st January 2021) - Arkell, P; Mahboobani, S; Wilson, R; Fatania, N; Coleman, M; Borman, A M; Johnson, E M; Armstrong-James, D P H; Abdolrasouli, A
Abstract: Prompt and reliable diagnosis of invasive pulmonary aspergillosis (IPA) is essential for early initiation of antifungal therapy. We evaluated bronchoalveolar lavage (BAL) fluid IMMY Sona Aspergillus lateral-flow assay (IMMY LFA) in 92 individuals with suspected pulmonary infection. Sensitivity and specificity (vs. host factor but no IPA) of BAL IMMY LFA for diagnosis of IPA in individuals with any European Organisation for Research and Treatment of Cancer-defied "host factor" were 67% and 85%, respectively. Performance appeared better in individuals with renal transplantation (100%, 100%), compared to those with hematological malignancy and/or allogenic stem cell transplantation (70%, 78%). We found BAL IMMY LFA to be a convenient and useful addition to our diagnostic armory for IPA. Lay abstract: We evaluated a new test for diagnosing invasive pulmonary aspergillosis from bronchoscopy samples. We tested 92 people and found that it was 67% sensitive and 85% specific (compared to diagnosis according to a set of internationally recognised criteria). We found this test convenient and useful.